Penggunaan Pendekatan Creative Problem Solving dalam Pengembangan Panduan Elearning Berbasis Moodle bagi Dosen Perguruan Tinggi Keagamaan Islam - Arif Rahman Hakim (LP. Ma'arif Janggan Magetan, 2022)
The use of Moodle-based elearning requires knowledge and skills to be able to build a good online learning page. Lecturers using Moodle-based elearning need proper guidance to be able to implement and create a good and attractive elearning portal display. This research is an R&D research. This study aims to develop Moodle-based elearning guidebook for lecturers using the Creative Problem Solving (CPS) approach. Data collection in this study was literature and questionnaires. The library method was used to find and collect various relevant sources and the questionnaire method was used to obtain data on the feasibility of the Moodle-based elearning guidebook using the Creative Problem Solving (CPS) approach developed. The results show that the process of developing Moodle-based elearning guidebook for lecturers using a creative problem solving approach includes seven stages; product design, design validation, design revision, small-scale trials, product revisions, large-scale trials, product revisions and product finals. The results of the validity of media experts get a score of 81.94 in the graphic aspect and 76.67 in the language aspect and both with proper and good predicates. The results of the validity of the material expert obtained a score of 78.86 in the content aspect and 82.64 in the presentation aspect and both with proper and good predicates. Moodle-based elearning guide for Religious College lecturers both from the media aspect and from the content aspect is good and feasible to use.